The effectiveness of face to face education using catharsis education action (CEA) method in improving the adherence of private general practitioners to recommend national guideline on management of tuberculosis in Bandung District Indonesia - Arisanti, Nita
Background: Mycobacterium tuberculosis has infected one-third of the world's population and imposes a global burden. In many countries, private health care providers are the gateway to health services for people with symptoms of TB. Targeting the private sector has been recommended in previous study to improve tuberculosis control. A brief face-to-face intervention using CEA Method with the physician, repeated at periodic intervals, seem to change physician's attitudes, beliefs and practice through persuasive communications. Objective: To determine the effectiveness of face to face education using Catharsis Education Action (CEA) Method in improving the adherence of private general practitioners to recommended national guideline on the management of tuberculosis patients (NTP) in Bandung District compared to brief reminder with provision of pamphlet. Methods: A randomized controlled trial of an educational intervention was done. Private general practitioners (PPs) from Bandung District were chosen and randomly assigned to one of two groups. For the intervention group, a session using the CEA method was used while brief reminder with provision of pamphlet was done for the comparative group. Main Outcome Measures: Adherence to recommended tuberculosis guideline (NTP). Results: A total of 82 PPs were included in the final analysis. Forty-three received CEA method while 39 received brief reminder with provision of pamphlet. Baseline knowledge among PPs in two groups was fairly good (mean score in CEA group is 64.95 and 76 in pamphlet group). In before - after analysis, there was statistically significant improvement on knowledge of TB guideline after intervention among PPs in CEA group with the changing score before and after intervention was 21.43 (p<0.05). The score on adherence to tuberculosis guideline before and after intervention among PPs in CEA group was maintained. When compared to pamphlet, the face to face education using CEA method was an effective as pamphlet in improving knowledge and adherence to TB guideline (p>0.05). Conclusions: Face to face education using Catharsis Education Action (CEA) method seem to be effective as brief reminder with provision of pamphlet in improving the adherence to recommended national guideline on the management of tuberculosis patients (NTP). CEA offers additional information that can be useful in designing intervention programs to improve NTP adherence. Education intervention in small does is less effective when compared to multiple implementation method.